CDCA7 facilitates MET1-mediated CG DNA methylation maintenance in centromeric heterochromatin via linker histone H1 - Shuya Wang; Tong Li; Matthew Naish; Russell Chuang; Evan K. Lin; Christian Fonkalsrud; Yan He; Suhua Feng; Ian R. Henderson; Steven E. Jacobsen (Proceedings of the National Academy of Sciences, 2025)
DNA methylation is a conserved epigenetic modification essential for maintaining genome stability. However, how methyltransferases maintain CG methylation within compact chromatin, including centromeres, remains unclear. In humans, CDCA7 is necessary for the inheritance of DNA methylation at juxta-centromeres. Mutations that impair its ability to bind chromatin result in Immunodeficiency, Centromeric Instability, and Facial Anomalies (ICF) syndrome, characterized by centromeric instability. To investigate whether CDCA7 function is conserved, we identified two Arabidopsis thaliana orthologs, CDCA7α and CDCA7β . The loss of both copies results in CG hypomethylation at pericentromeric regions and centromeric satellite repeat arrays. Machine learning analysis suggested that heterochromatic nucleosomes, with enrichment of H1, H2A.W, and H3K9me2, depend heavily on CDCA7 proteins for CG methylation maintenance of the associated DNA. Loss of H1 restores heterochromatic DNA methylation in cdca7α cdca7β mutants, indicating that CDCA7α and CDCA7β mainly remodel H1-containing nucleosomes for methyltransferases to access DNA. Notably, in h1.1 h1.2 mutants, CG methylation shows a significant increase in centromeres, which reveals a new inhibitory role of H1 in DNA methylation maintenance within satellite repeat arrays. Centromeric DNA hypermethylation is lost in h1.1 h1.2 cdca7α cdca7β quadruple mutants, demonstrating that CDCA7α and CDCA7β can act independently of H1 to enhance MET1 activity at nucleosomes. Overall, these findings establish CDCA7α and CDCA7β as conserved regulators of DNA methylation within heterochromatin and centromeric satellite repeat arrays.